Pengaruh Teknologi Informasi dan Komunikasi terhadap Produk Domestik Regional Bruto Indonesia - Muhammad Adi Imam Fikri; Dwini Handayani (Syntax Corporation, 2023)
The urgency of ICT development and interconnectivity among regions has recently gained attention. This research aims to mediate and assess the progress of ICT by analyzing factors that can impact the economy. Consequently, it can be observed how ICT influences the economy of each Indonesian province. This study is conducted to contribute and enrich empirical studies on Regional Gross Domestic Product (GDP) and its influencing factors. It provides insights for policymakers, especially the central and local governments, in stimulating regional economies and gaining a different perspective on ICT and its impact on GDP. However, to capture the indirect effects of development on the economy, a lag of one year is applied to each variable. The data period for the GDP variable is limited to 2017-2021, while for other variables, it is 2016-2020, aligning with the research objective of examining the economic development overview. These data are then processed using panel data regression. Based on descriptive and statistical analysis, it can be concluded that the percentage of the population aged 5 and above accessing the internet has a significant contribution to the economy as depicted by GDP. However, there are other more significant factors contributing to Indonesia's GDP.